2006
DOI: 10.1113/jphysiol.2006.121970
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in ventilation during normoxia and acute hypoxia in the rat: implication for a sensitive period

Abstract: Previously, we found heightened expression of inhibitory neurochemicals and depressed expression of excitatory neurochemicals with a sudden drop in metabolic activity around postnatal day (P) 12 in rat brainstem respiratory nuclei, suggesting that this period is a critical window during which respiratory control or regulation may be distinctly different. To test this hypothesis, the hypoxic ventilatory responses (HVR) to 10% oxygen were tested in rats every day from P0 to P21. Our data indicate that (1) during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
110
5
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(134 citation statements)
references
References 62 publications
18
110
5
1
Order By: Relevance
“…Dynamic compliance was estimated from data obtained during a single-frequency forced oscillation maneuver, using a mathematical model-fitting technique according to the specifications of Scireq Inc. (Montreal, PQ). To determine ventilator settings, we started with the normal breathing frequency of a 8-d-old rat [ϳ160/min (15)] and adjusted V T and positive end expiratory pressure (PEEP) to achieve normal blood gases. The V T and PEEP values for this frequency were ϳ12.5 mL.kg Ϫ1 and 2 cm H 2 O, respectively.…”
Section: Animalsmentioning
confidence: 99%
“…Dynamic compliance was estimated from data obtained during a single-frequency forced oscillation maneuver, using a mathematical model-fitting technique according to the specifications of Scireq Inc. (Montreal, PQ). To determine ventilator settings, we started with the normal breathing frequency of a 8-d-old rat [ϳ160/min (15)] and adjusted V T and positive end expiratory pressure (PEEP) to achieve normal blood gases. The V T and PEEP values for this frequency were ϳ12.5 mL.kg Ϫ1 and 2 cm H 2 O, respectively.…”
Section: Animalsmentioning
confidence: 99%
“…We hypothesized that at and around P12 is a sensitive period in the postnatal development of the rat's respiratory control network, when a transient dominance of inhibitory over excitatory neurotransmission renders the animals less capable of overcoming exogenous respiratory stressors. Our subsequent ventilatory studies revealed striking changes in normoxic ventilation as well as hypoxic ventilatory response (HVR) at and around P13, with a peak in respiratory frequency and a transient peak both in tidal volume (VT) and minute ventilation (V E) under normoxia (32). The body temperature also peaked at P13.…”
mentioning
confidence: 99%
“…The body temperature also peaked at P13. Significantly, the lowest HVR (decreased frequency response and the lowest VT response; therefore, the lowest V E response) was also at P13 (32). Thus the end of the second postnatal week is likely to be a critical period during which the animals are less responsive to external stressors, such as hypoxia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Why animals did not hyperventilate at P12 is unknown, but it may reflect either the high tidal volume observed in control animals (probably a result of the highly variable breathing pattern and the switch from neonatal to adult breathing in this age group), which stabilised during CO 2 exposure, or a window of development where these animals are more vulnerable to hypoxia. Such a window of vulnerability has been reported in P12 rats with an absence of increasing V E /V O2 , due to a decrease in tidal volume and a comparatively weak metabolic response to hypoxia; a response that was different from that in the rest of the first 3 postnatal weeks (Liu et al, 2006). In addition, a reduction in excitatory and an increase in inhibitory neurotransmitters (Wong-Riley and Liu, 2005) as well as a significant decline in tryptophan hydroxylase and serotonin transporter immunoreactivity (Liu and Wong-Riley, 2010b;Liu and Wong-Riley, 2010a) further suggests that normal development can contribute to a narrow window of vulnerability in rats at this age (P12), though lack of proper controls limits the interpretation of these developmental studies.…”
Section: The Journal Of Experimental Biology 215 (24)mentioning
confidence: 98%